Screening of Blood Hemoglobin Levels for Filling Station Operators in Gresik - Nastiti Trikurniadewi; Zufra Inayah (Kontribusia : Research Dissemination for Community Development, 2023)
Filling station operators are employee who spend a lot of time outdoors exposed to fuel oil, dust and vehicle fumes. The filling station operator's work environment has risks to health, including anemia. Anemia is a condition that hemoglobin (Hb) levels in the blood below the minimum limit. This community service activity aims to provide anemia education and conduct Hb level screening for filling station operators in Gresik. Examination of the filling station operator's Hb level was carried out using a simple random sampling technique with a cross-sectional time approach. The number of respondents was as much as 69 filling station operators from 7 filling stations in Gresik. The results of examination of Hb levels showed that 11.6% of respondents had Hb levels below the minimum limit. The data obtained were analyzed statistically using the Fisher test, the results showed that there was no relationship between Hb levels of filling station operators and gender, age, length of work (years), duration of work (hours/week), and use of Personal Protective Equipment (PPE). Nonetheless, these four variables have a prevalence risk (PR) of anemia, namely gender (PR=2.347), age (PR=1.17), length of work (PR= 0.867) and duration of work (PR=1.240), so that operators filling stations have a risk of anemia. Administrative forms of prevention can be carried out with medical check-ups routine. Health education is also needed as a preventive measure to maintain employee health.